Buccal Mucosal Grafts in Surgery of Urethral Tuberculosis - A. А. Volkov; O. N. Zuban; N. V. Budnik; A. V. Muziev (Туберкулез и болезни лёгких)
The objective of the study: to analyze the effectiveness of surgery in patients with post-tuberculous urethral strictures/obliterations when buccal mucosa is used for reconstruction.Subjects and Methods. The surgery was performed in 5 patients with sequelae of specific urethral lesions such as extended strictures or obliterations. All patients underwent ureteroplasty with buccal graft (BG). In 4 cases, tubularized BG was used, and in 1 case it was onlay one.Results. The patients were followed up for 3-55 months. Over this period no relapse or severe complications were observed.Conclusion. Buccal ureteroplasty is a promising method for the treatment of post-tuberculous urethral strictures/obliterations with a high risk of other reconstructive surgeries.